Casa en Tavira (1998)
Vivienda ubicada en lo alto de una colina, utilización de varios volúmenes para cumplir el programa.
Keywords: MOURA, EDUARDO SOUTO DE; TAVIRA; ALGARVE; PORTUGAL; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS